THE RELATIONSHIP OF AGE AND INFORMATION SOURCES TOWARDS MOTHER'S KNOWLEDGE ABOUT GIVING COLOSTRUM TO NEWBORN BABIES AT THE SURADITA CLINIC, TANGGERANG DISTRICT - Farlikhatun, Lili; Sumiyati, Lilis (HEARTY, 2024)
Giving colostrum has recommended by the world health agency World Health Organization (WHO) since in 2001 ( Roesli, 2014). Research conducted in the Netherlands states that exclusive breastfeeding _ specifically colostrum relate with decline risk death babies caused by infection _ channel respiratory and gastrointestinal disorders. The research results also stated that breastfeeding since _ day First birth baby can reducing 16% of neonatal deaths and reducing 22% of neonatal deaths if baby breastfed in first hour _ birth (Edmond, 2019). Colostrum is stage I breast milk day First until day fourth. After labor composition colostrum experience change. Colostrum colored yellow golden due to its height composition of fat and cells life (Septiani & Ummami, 2020). Observation Introduction to the Clinic Suradita Already give information and knowledge about colostrum, only just Not yet fully understood by future mothers _ _ _ giving birth at the clinic Suradita. Only 20 % understand importance colostrum at the Clinic Suradita This. Research design This use design research descriptive with approach quantitative cross sectional where the data is variable researched simultaneously. In research This its population is All mothers who have baby new born at the Clinic Suradita Tangerang at the time done study. Deep sample study This totaling 30 babies. Data analysis was carried out with SPSS computer program assistance. Analysis used _ is analysis univariate and analysis bivariate. Statistical test results (chi square) showing p value = 1.00, mean p value > alpha value (0.05), with thereby so his decision is Ho accepted and Ha rejected. In conclusion is No there is connection significant age _ with giving colostrum. Statistical test results (chi square) showing p value = 0.0 1, means p value < alpha value (0.05), with thereby so his decision is Ho rejected and Ha accepted. In conclusion is there is significant relationship between knowledge and giving colostrumStatistical test results (chi square) showing p value = 0.0 1, means p value < alpha value (0.05), with thereby so his decision is Ho rejected and Ha accepted. In conclusion is there is significant relationship source _ information with giving colostrum. From the conclusion the, so recommended Clinic Suradita increase service with give knowledge and information about importance giving colostrum in new babies _ born. And always give new baby _ born in the mother's chest so that the baby can direct breast-feed.